2018
DOI: 10.1016/j.anifeedsci.2018.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Moderated milk replacer restriction of ewe lambs alters gut immunity parameters during the pre-weaning period and impairs liver function and animal performance during the replacement phase

Abstract: Undernutrition during the first stages of life may impair maturation of the immune system, harming the health status permanently. Thus, the aim of the present study was to define the impact of moderated milk replacer (MR) restriction during the artificial rearing period on the gut-associated lymphoid tissues of pre-weaned ewe lambs and long-term effects on biochemical profile and animal performance during the replacement period. Forty female Assaf lambs [average live body weight (LBW) 4.73 ± 0.116 kg] were pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 31 publications
0
13
0
1
Order By: Relevance
“…Regarding lambs, several studies have shown that metabolic programming events are caused by early feed restriction (Davies and Owen, 1967;Greenwood et al, 2004;Galvani et al, 2014), with negative long-term effects after the period of feed restriction. In this sense, previous studies have demonstrated negative consequences not only on the health status (Frutos et al, 2018) and feed efficiency traits (Santos et al, 2018c,d), but also on the onset of puberty in replacement ewes lambs (Santos et al, 2018c). However, even though we have found several studies in children (Ruchat et al, 2014), cattle (Soberon et al, 2012;Soberon and Van Amburgh, 2013;Alexandre et al, 2015), and pigs (Vincent et al, 2015), to our knowledge no studies have described the effects of early feed restriction at the gene expression level in artificially reared female Assaf lambs.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Regarding lambs, several studies have shown that metabolic programming events are caused by early feed restriction (Davies and Owen, 1967;Greenwood et al, 2004;Galvani et al, 2014), with negative long-term effects after the period of feed restriction. In this sense, previous studies have demonstrated negative consequences not only on the health status (Frutos et al, 2018) and feed efficiency traits (Santos et al, 2018c,d), but also on the onset of puberty in replacement ewes lambs (Santos et al, 2018c). However, even though we have found several studies in children (Ruchat et al, 2014), cattle (Soberon et al, 2012;Soberon and Van Amburgh, 2013;Alexandre et al, 2015), and pigs (Vincent et al, 2015), to our knowledge no studies have described the effects of early feed restriction at the gene expression level in artificially reared female Assaf lambs.…”
Section: Introductionmentioning
confidence: 69%
“…Accumulated MR intake and animal performance of these preweaning lambs selected for omics (8 preweaning lambs in total) are summarized in Table 2 and Figure 1, whereas the rest of parameters measured at slaughter (16 preweaning lambs in total) are described in Santos et al (2018c). The nonslaughtered animals (24 lambs in total) were weaned and fed ad libitum a TMR to study the effects of metabolic programming provoked by early feed restriction during the replacement phase (Frutos et al, 2018;Santos et al, 2018c). In the present study, only those data regarding liver transcriptomic and proteomic profiles of preweaning lamb (those slaughtered) are presented.…”
Section: Animal Diets and Samplingmentioning
confidence: 99%
“…Regarding lambs, several studies have shown that metabolic programming events are caused by early feed restriction , with negative long-term effects after the period of feed restriction. In this sense, previous studies have demonstrated negative consequences not only on the health status (Frutos et al, 2018) and feed efficiency traits (Santos et al, 2018c,d), but also on the onset of puberty in replacement ewes lambs . However, even though we have found several studies in children , cattle Soberon and Van Amburgh, 2013;, and pigs , to our knowledge no studies have described the effects of early feed restriction at the gene expression level in artificially reared female Assaf lambs.…”
Section: Introductionmentioning
confidence: 88%
“…Accumulated MR intake and animal performance of these preweaning lambs selected for omics (8 preweaning lambs in total) are summarized in Table 2 and Figure 1, whereas the rest of parameters measured at slaughter (16 preweaning lambs in total) are described in . The nonslaughtered animals (24 lambs in total) were weaned and fed ad libitum a TMR to study the effects of metabolic programming provoked by early feed restriction during the replacement phase (Frutos et al, 2018;. In the present study, only those data regarding liver transcriptomic and proteomic profiles of preweaning lamb (those slaughtered) are presented.…”
Section: Animal Diets and Samplingmentioning
confidence: 99%
See 1 more Smart Citation